Preliminary Survey of Aedes sp. Larvae in Mosques of Banda Aceh During Ramadan 2025 - Emil, Muhammad Farhan Putra; Emil, Raudhah Putri Emil (Journal of Biotechnology and Natural Science, 2025)
The Aedes sp. mosquito is the main vector of dengue fever that breeds in environments with suitable breeding sites. Mosques, as places of worship with bathroom facilities and water storage containers, have the potential to become breeding grounds for Aedes sp. mosquitoes. This study aims to identify the presence of Aedes sp. larvae in mosque bathrooms in Banda Aceh during Ramadan 2025. A total of 45 mosques across nine districts were surveyed using a random sampling method (data representation with equal chances of selection). Observations focused on water storage containers, ventilation, lighting, and the availability of container covers. Larvae and water samples were collected and analyzed in the laboratory. The findings confirm the presence of Aedes aegypti and Aedes albopictus larvae, with a higher prevalence of Aedes aegypti due to its preference for indoor breeding sites. Poor ventilation, inadequate lighting, and uncovered water storage containers were key factors contributing to mosquito breeding. These results highlight the potential risk of dengue transmission in mosques, emphasizing the need for improved water management and preventive measures to ensure worshippers' safety. Strengthening mosquito control efforts in places of worship is essential to minimize dengue fever outbreaks, particularly during periods of increased human activity such as ramadan.